THE EFFECT OF PROFITABILITY, FIRM SIZE, FIRM GROWTH, AND DIVIDEND POLICY ON STOCK PRICES WITH CAPITAL STRUCTURE AS MODERATING VARIABLES - Pandia, Cory (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study is profitability, firm size, firm growth, and dividend policy on stock prices with capital structure as a moderating variable. The population in this study are telecommunications companies listed on the Indonesia Stock Exchange in the period 2011-2018. The sample selection method uses a purposive technique. The samples used were 4 companies. The method used in this research is panel data regression method with a significance level of 5% using the common effect model (CEM). Hypothesis testing uses t test, f test, and interaction test. The results showed that partially profitability had a positive and significant effect on stock prices, while company size and dividend policy had a negative and significant effect on stock prices and company growth had a positive and not significant effect on stock prices. The second hypothesis testing shows that the capital structure is not able to moderate the relationship between profitability, firm size, and firm growth on stock prices while the capital structure is able to moderate the relationship between dividend policy on stock prices.